Experimental Investigation of by-Product Hydrogen Gas in the Harvesting Process of Dunaliella salina using a Non-Sacrificial Cathode - Purwono Purwono; Hadiyanto Hadiyanto; Marcelinus Christwardana; Widayat Widayat; Mochamad Arief Budihardjo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Hydrogen gas is considered a pollution-free fuel in the future. However, the EC process using these non-sacrificial electrodes requires further research especially for the production of dissolved hydrogen gas and the efficiency of microalgae harvesting. The purpose of this study was to investigate the concentration of dissolved hydrogen gas produced from the harvesting process of Dunaliella salina microalgae species using EC and ORP concentrations including pH, harvesting efficiency due to voltage variations and harvesting time using EC with non-sacrificial electrodes. D salina harvesting using EC reactor made of cylindrical borosilicate glass. Spiral-shaped type 304 stainless steel (non-sacrificial) serves as the cathode and solid cylindrically-shaped Fe serves as the anode. The voltage set varies between 16, 18, and 20 Volts, while the electrolysis time is varied between 1.3.5 minutes. The results showed that the highest dissolved hydrogen concentration of 820 ppb (0.820 ppm) produced from the EC process used 18 V for 3 minutes. The volume of gas could not be measured because most of the hydrogen gas was dissolved in the D salina culture, so it was not enough to evaporate within 3 minutes. The maximum ORP concentration of -413 mV resulting from the EC process uses 18 V for 3 minutes. When hydrogen gas is present in a solution, it can decrease the ORP value of the solution. At EC time with non-sacrificial electrodes for 5 minutes managed to harvest D salina 50.79%; 61.90%; 74.60% at voltages of 16 V, 18V, and 20 V respectively.